PENGARUH PROGRAM SETEKSI MASUK TERHADAP PRESTASI BELAJAR SISWA SMU - Supriyoko Supriyoko (Jurnal Kependidikan, 2000)
The purpose of the research is to disclosure the influence of using entry seleition  (NEM) ii  'physiial  'is'to  program based on the original government examination score iuitor  cindttion  high school (SLTP), abstract reasoningability, and for  senior high school SMU) students. The method used compute thi relationship of the entry selection program toward student achievement in Mathematics  and English. The model of the research is a case study at the SMU Tamansiswa Bandung involving a data analysis  ut d  1o,  for  the whole population of 454 students. The analysis technique this research is Product Moment Analysis and Linear Regression Analysis. From the data oulysis result it was concluded that entry seleition program has a positive and very significant effect  achievembnt. Generally speaking it can be concluded that the entry selection  program  for  for  the student fuIU which consist of NEM SLTP, abstract reasoning'ability, and pttysical condition is very  selection system ofthe new students.